The Psychological Empowerment and its Relationship to the Quality of Job Life for the Palestinian Police Personnel in Hebron Governorate - Masri, Ibrahim Sulaiman; Makhamreh, Kamal (Journal of Educational and Psychological Sciences, 2021)
The study attempts to identify the psychological empowerment and its relationship to the quality of job life for the Palestinian police personnel in Hebron governorate. The study population consisted of (835) male and female police officers, whereas the study sample consisted of (161), who were chosen by a simple random sample method and the results were as follows: The level of psychological empowerment of Palestinian police personnel was high, and there were statistically significant differences at the level (α≤0.05) in the averages degree of psychological empowerment over the total score due to the years of experience variable in favor of police personnel who have (11 years or more) of experience. There are also statistically significant differences at the level (α≤0.05) in the averages of the degree of psychological empowerment of police officers over the total score due to the educational level variable. The degree of job quality of the Palestinian police personnel was high. There were no statistically significant differences at the (α≤0.05) level in the averages of the degree of job quality on the total degree due to the variables of years of experience and educational level. Also, there is a statistically significant relationship at the level of significance (α≤0.05) between the total score of the psychological empowerment averages and the quality of work life for police personnel. The study recommended the need to reinforce the status of Palestinian police by maintaining the quality of their career and enabling them to continually improve their performance.